Additions to the genus Periconia from northern Thailand - Tian, Xingguo; Tibpromma, Saowaluck; Karunarathna, Samantha C.; Dai, Dongqin; Bao, Danfeng; Mapook, Ausana; Ruvishika S. Jayawardena (Phytotaxa, 2022)
Pineapple is one of the economically important fruits in Chiang Rai Province but few studies have been carried out on fungal saprobes on this plant. During a survey of fungal saprobes on pineapple, several dead leaves covered by hyphomycetous fungi with effuse colonies, dark brown to black on the host substrate were collected. Phylogenetic analyses of combined ITS, LSU, SSU, and TEF1-α sequence data revealed that our fungal collections are members of Periconia. Based on morphological comparisons and multi-locus phylogeny we introduce a new species (Periconia ananasi sp. nov.) and a new host and geographic record for Periconia epilithographicola. The results expand our knowledge of microfungi on pineapple. Full descriptions, illustrations, and multi-locus phylogeny of the taxa studied are provided.